The Impact of Organizational Communication, Employee Training and Development on Employee Performance In Air Cargo Export Company - Sopianti, Eva; Winanti; Wiki Dermawan Siregar; Sri Komalasari4; Ariadin Nurfy (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
Organizational communication, employee training and development are crucial in determining a company's success, particularly in logistics companies operating in the export sector. The growing globalization and increasingly fierce competition in logistics demand companies, such as air cargo export firms, to improve the quality of their human resources to enhance service quality for customers and achieve competitive advantages, enabling them to compete globally. The research variables analyzed include Organizational Communication (X1), Employee Training and Development (X2), and Employee Performance (Y). The sampling method used is probability sampling, specifically through simple random sampling. The data collection techniques employed in this study are interviews and questionnaires. The collected data were analyzed via SSPS version 22. The results of this study show a multiple correlation coefficient of 0.858, indicating a powerful influence. The numerous determination coefficient of this research is 0.736, meaning that organizational communication and training and development have a 73.6% effect on employee performance. In comparison, the remaining 26.4% is influenced by other variables not included in this study. The results of the F-test indicate a significant simultaneous influence because the F calculated > F table (62.585 > 3.280).